Building up Teacher’s Awareness about Burnout to Support Mental Health - Lita Patricia Lunanta; Reneta Kristiani; Gracia Samuela Kiswanto; Renata Raissa Sondakh (MITRA: Jurnal Pemberdayaan Masyarakat, 2022)
Teacher’s job requirements are not only in teaching but also in social interaction and administrative tasks and various knowledge and other supporting skills. High job demands and the dynamic experiences that teachers need to accomplish everyday could make them prone to burnout. Teachers under the organization of Majelis Pendidikan Indonesia (MPK) had unique characteristics and challenges that made them prone to burnout. This psychoeducation was needed to achieve the aim of building knowledge about burnout and all other aspects related to burnout. It was hoped that this knowledge could help teachers prevent the occurrence of burnout. With methods of presentations and online interactive discussion, the presenter discussed some of the things that can be done at an organizational level and individually. The comparison of the pre-test and post-test score showed an increase of understanding (the average of pretest score is 72.24 and posttest score is 77.67 of 100) of the materials around burnout and its aspects. Participants also gave positive feedback on an evaluation survey with 94% of the participants felt that they gained new knowledge and felt satisfied with the whole psychoeducation activities. For following up, it was suggested to include a method of small group discussion and included a practical manual about techniques for overcoming burnout for teachers. Furthermore, the systemic intervention urge to be done to develop burnout intervention service flow becomes more comprehensive.